Integrated geophysical‐petrological modeling of lithosphere‐asthenosphere boundary in central Tibet using electromagnetic and seismic data - Jan Vozar; Alan G. Jones; Javier Fullea; Matthew R. Agius; Sergei Lebedev; Florian Le Pape; Wenbo Wei (Geochemistry, Geophysics, Geosystems)
Abstract We undertake a petrologically driven approach to jointly model magnetotelluric (MT) and seismic surface wave dispersion (SW) data from central Tibet, constrained by topographic height. The approach derives realistic temperature and pressure distributions within the upper mantle and characterizes mineral assemblages of given bulk chemical compositions as well as water content. This allows us to define a bulk geophysical model of the upper mantle based on laboratory and xenolith data for the most relevant mantle mineral assemblages and to derive corresponding predicted geophysical observables. One‐dimensional deep resistivity models were derived for two groups of MT stations. One group, located in the Lhasa Terrane, shows the existence of an electrically conductive upper mantle layer and shallower conductive upper mantle layer for the other group, located in the Qiangtang Terrane. The subsequent one‐dimensional integrated petrological‐geophysical modeling suggests a lithosphere‐asthenosphere boundary (LAB) at a depth of 80–120 km with a dry lithosphere for the Qiangtang Terrane. In contrast, for the Lhasa Terrane the LAB is located at about 180 km but the presence of a small amount of water in the lithospheric mantle (<0.02 wt%) is required to fit the longest period MT responses. Our results suggest two different lithospheric configurations beneath the southern and central Tibetan Plateau. The model for the Lhasa Terrane implies underthrusting of a moderately wet Indian plate. The model for the Qiangtang Terrane shows relatively thick and conductive crust and implies thin and dry Tibetan lithosphere.